The Critical Role of Nurses in Caring for Preterm Infants with Respiratory Distress Syndrome Receiving Non-Invasive Ventilation: A Case Study in NICU - Rattanachamnongk , Prattana (Siriraj Medical Bulletin, 2025)
Respiratory Distress Syndrome (RDS) is a significant and common complication among preterm infants, primarily resulting from pulmonary immaturity and underdeveloped respiratory function, which lead to inefficient gas exchange. Currently, the use of non-invasive ventilation (NIV) has become an essential therapeutic strategy, as it reduces the need for endotracheal intubation and decreases the risk of long-term complications such as bronchopulmonary dysplasia (BPD). Nursing care plays a crucial role in the close monitoring and management of these infants to ensure safety and effective treatment outcomes. This case study involved two preterm infants with RDS who were admitted to the Neonatal Intensive Care Unit (NICU) at Siriraj Hospital. The first case was a male infant born at 30 weeks’ gestation, and the second was a female infant born at 32 weeks’ gestation. Both were managed with NIV as primary respiratory support. The results demonstrated that both infants were able to maintain adequate oxygenation without the need for intubation. No severe complications were observed, except for mild abdominal distension and localized nasal interface pressure marks, which were effectively managed with appropriate nursing interventions. The findings highlight that NIV is an effective strategy for supporting respiration in preterm infants with RDS and helps reduce the need for invasive ventilation. Comprehensive nursing care, including continuous assessment, vigilant monitoring, and timely management of complications, plays a pivotal role in ensuring the safety and improving both the short-term and long-term outcomes of preterm infants with respiratory distress.